In Vivo and In Vitro Efficacy of Minocycline-Based Combination Therapy for Minocycline-Resistant Acinetobacter baumannii - Yang, Ya-Sung (Antimicrob Agents Chemother, 2016)
Minocycline-based combination therapy has been suggested to be a possible choice for the treatment of infections caused by minocycline-susceptible Acinetobacter baumannii, but its use for the treatment of infections caused by minocycline-resistant A. baumannii is not well established. In this study, we compared the efficacy of minocycline-based combination therapy (with colistin, cefoperazone-sulbactam, or meropenem) to that of colistin in combination with meropenem for the treatment of minocycline-resistant A. baumannii infection. From 2006 to 2010, 191 (17.6%) of 1,083 A. baumannii complex isolates not susceptible to minocycline from the Taiwan Surveillance of Antimicrobial Resistance program were collected. Four representative A. baumannii isolates resistant to minocycline, amikacin, ampicillin-sulbactam, ceftazidime, ciprofloxacin, cefepime, gentamicin, imipenem, levofloxacin, meropenem, and piperacillin-tazobactam were selected on the basis of the diversity of their pulsotypes, collection years, health care setting origins, and geographic areas of origination. All four isolates had tetB and overexpressed adeABC, as revealed by quantitative reverse transcription-PCR. Among all minocycline-based regimens, only the combination with colistin produced a fractional inhibitory concentration index comparable to that achieved with meropenem combined with colistin. Minocycline (4 or 16 μg/ml) in combination with colistin (0.5 μg/ml) also synergistically killed minocycline-resistant isolates in time-kill studies. Minocycline (50 mg/kg of body weight) in combination with colistin (10 mg/kg) significantly improved the survival of mice and reduced the number of bacteria present in the lungs of mice compared to the results of monotherapy. However, minocycline (16 μg/ml)-based therapy was not effective at reducing biofilm-associated bacteria at 24 or 48 h when its effectiveness was compared to that of colistin (0.5 μg/ml) and meropenem (8 μg/ml). The clinical use of minocycline in combination with colistin for the treatment of minocycline-resistant A. baumannii may warrant further investigation.